(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The development of women’s sports in Uzbekistan is gaining momentum, reflecting global trends in gender equality and athletic opportunities. Over the past decades, significant progress has been made in creating a supportive environment for female athletes, including government programs, increased investment, and a growing public interest in women’s sports. However, numerous challenges persist, including societal expectations, limited financial resources, and a lack of infrastructure dedicated to women’s sports. This paper examines the current state of women’s sports in Uzbekistan, identifies key barriers to progress, and explores strategies to enhance female participation in competitive and recreational sports. By analyzing policies, economic factors, and social attitudes, the study aims to provide a comprehensive overview of the future prospects of women’s sports in the country. The findings suggest that sustained government support, media representation, and grassroots initiatives are crucial to fostering long-term growth and inclusivity in women’s sports.